The effects of SiO2@Y2O2S:Eu3+ phosphor on the optic characteristics of white light-emitting diodes - Van Liem Bui; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
The study investigated the effectiveness of coating silica nanoparticles (SiO2) and resin-silica nanocomposites poly methyl methacrylate (PMMA)-silicaover the surface of Y2O2S:Eu3+ red phosphors. The purpose of this surface coating is to enhance the optical properties, including the photoluminescence (PL) and long-term stability, of Y2O2S:Eu3+. Two methods used to coat the phosphor with 5-mm silica nanoparticles are dip-coating and sol-gel (Stöber) methods. SiO2 nanoparticles were formed via hydrolysis and condensation reactions, while radical polymerization was performed to fabricate the poly (1-vinyl-2-pyrrolidone). The Y2O2S:Eu3+ surface coating of PMMA-silica composite was performed via two reactions. One is the reaction of SiO2 nanoparticles with methyl methacrylate (MMA) monomer, and the other is MMA-tetraethyl orthosilicate (TEOS) reaction. The results showed that by using the latter method, Y2O2S:Eu3+ yielded better PL and long-term stability. Additionally, surface coating with the PMMA-SiO2 nanocomposite using the second technique resulted in 5% enhancement in PL and stabilized the cathode luminescence (CL) intensity of Y2O2S:Eu3+, compared to those properties of uncoated Y2O3S:Eu3+ phosphor particles.